Improvement of organizational work on the implementation of architectural and construction control - Zeltser, R.Y.; Kolot, M.A.; Panasyuk , I.O. (Ways to Improve Construction Efficiency, 2022)
Urban reform has passed the next stage: State Architectural and Construction Inspectorate has been officially liquidated, a new body of the State Inspectorate for Architecture and Urban Planning (SIAUP) is starting work. This is one of the important steps in reforming the construction industry. Innovations eliminate the influence of the human factor, direct contact with officials, document management will be translated into digital format. The portal of the Unified State Electronic System in the field of construction is already working. The main task of SIAUP is the implementation of state policy on architectural and construction control and supervision, including: implementation of state architectural and construction control and supervision, licensing of economic activities for the construction of facilities that belong to the class of consequences (responsibilities). projects with medium (SS2) and significant (SS3) consequences, and control over the observance by business entities of licensing conditions for conducting economic activities for the construction of facilities that by class of consequences (liability) belong to facilities with medium (SS2) ) and significant (SS3) consequences. SIAUP has the authority to conduct inspections; issue instructions to eliminate violations of legal requirements, stop preparatory and construction works, eliminate violations of licensing conditions; carry out licensing; cancels or suspends the decisions of the objects of supervision, etc. SIAUP exercises its powers directly and through duly established territorial bodies. The duty to monitor compliance with the law in urban planning is the responsibility of local authorities. Private companies will appear on the market, which will be able to perform the function of state control. SIAUP is headed by a chairman, who is appointed and dismissed by the Cabinet of Ministers of Ukraine.